Liberdade e responsabilidade em o ser e o nada de Jean-Paul Sartre: perspectiva ética de um engajamento intelectual - Fernandes, Luciana Lima (2015)
The philosophy of Jean-Paul Sartre (1905 - 1980) is commonly divided into two stages, the first facing the most philosophical questions, ahistorical being and metaphysical and with Being and Nothingness (1943) as central work, while the second I would be more concerned with man in history and with a more practical philosophy, and dialectical reason of Criticism (1960) as the main work. The idea of our work is denying such bias, arguing that the work 1943 is far from being ahistorical or metaphysics. Rather there his conception of freedom is necessarily linked to a situation, it is focused on action and is related to the responsibility of men in each of these situations. To defend our position, we will analyze some biographical elements that indicate the intellectual engagement of the philosopher, whether in his public life, both as a writer and investigate their conceptions of freedom and responsibility present in Being and Nothingness. It is thus relating the analysis of his experience as an intellectual and as engaged writer to the study of freedom and responsibility that seek to understand the philosophy of Sartre as a practical philosophy, history and focused on the action, thus outlining the first steps towards construction of an ethic.